The other Copts: Between sectarianism, nationalism and catholic Coptic activism in Minya. - Torres Gutiérrez, Ana Carol (AUC Knowledge Fountain, 2017)
The partnership between the Coptic Orthodox Church and the Egyptian State has been a political technique that has left little space for religious diversity and has overshadowed other Egyptian minorities. Eschewing this dichotomous illusion and blowing the dust off of Missionary Studies that has left Catholic Copts in the past, this ethnographic study gives an account of the life of a Catholic Coptic NGO, the Jesuit Brothers Association for Development (JBAD), within the context of the uncontested capital of sectarian violence in Egypt: Minya. Using participant observation, focus groups, and interviews, this study intends to shed a light on the ways through which sectarian boundaries and identity politics have affected Catholic Copts engaging in activism in the post-2011 era. Particularly, this study explores how three sectarian lines are negotiated in the everyday life of this Catholic Coptic NGO. It explores the convenience and sponsorship that being part of a transnational Catholic Church gives Catholic Coptic institutions such as the JBAD yet its ritualistic remoteness from other types of Catholicism; the negotiation of its common roots with the Coptic Orthodox vis-Ã -vis their perplexity of their historic rivalry; and the ways in which Catholic Copts relate with the Muslim majority and the Egyptian State that vacillate between spiritual service and sectarian violence. This thesis questions how still today Catholic Copts are perceived as a foreign or fabricated minority while they are actually industrious and even nationalist citizens. Although this research subscribes to the literature that addresses the transitions from Mission to NGO's that took place at the end of WWII, in the particular case of Catholic Copts, it proposes a change of scholar discourse from Missionary Studies into those of nationalism and citizenship.